Resting State EEG in Exercise Intervention Studies: A Systematic Review of Effects and Methods - Gramkow, Mathias Holsey; Hasselbalch, Steen Gregers; Waldemar, Gunhild; Frederiksen, Kristian Steen (Frontiers in Human Neuroscience, 2020)
Background Exercise has been shown to alter brain plasticity and is explored as a therapeutic intervention in a wide variety of neurological diseases. Electroencephalography (EEG) offers an inexpensive method of studying brain electrocortical activity shortly after exercise and thus offers a way of exploring the influence of exercise on the brain. We conducted a systematic review to summarize the current body of evidence regarding methods of EEG analysis and the reported effects of exercise interventions on EEG. Methods PubMed, Web of Science and EMBASE were searched for studies investigating resting state EEG in exercise intervention studies carried out in participants > 17 years of age and with no history of epilepsy. Further, studies solely investigating event-related potentials as an outcome measure were excluded. Relevant data were extracted, and a risk-of-bias assessment was carried out using the Cochrane risk-of-bias tool. A qualitative synthesis of results was carried out. A protocol for the systematic review was uploaded to https://www.crd.york.ac.uk/PROSPERO/ (ID: CRD42019134570) and the Preferred Reporting Items for Systematic Reviews (PRISMA) statement was followed. Results Out of 1993 records screened, 54 studies were included in a final qualitative synthesis with a total of 1445 participants. Our synthesis showed that studies were mainly carried out using frequency analysis as an analytical method. Generally, findings across studies were inconsistent, although temporary changes in EEG microstates and alpha peak shifts were found in a small number of studies. Moreover, studies were mainly of low quality and usually carried out in small populations. Conclusions Few, temporary changes in the EEG were elicited by exercise interventions. Future studies should provide biologically sound hypotheses underlying assumptions, include larger populations and use standardized EEG methods to increase replicability. EEG remains an interesting methodology to examine the effects of exercise on the brain.